Pengaruh Angin Permukaan dan Kelembapan Udara Terhadap Suspended Particulate Matter (SPM) di Sorong Periode Januari – Juli 2019 - Nuryanto; Haris Munandar Gultom; Shel Melinda (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2021)
Sorong has the characteristics of a dense population, high community mobility, and the growth of motorized vehicles. The increasing rate of mobility in Sorong has the potential to increase air pollution as well. One of the air pollution measured by the Global Atmosphere Watch (GAW) Sorong Station is Suspended Particulate Matter (SPM). SPM is solid and liquid particles that float in the air for a relatively long period of time, then the presence of meteorological parameters also plays an important role in increasing and pollutant sources in Sorong. This study aims to determine the level of SPM concentration, determine the source of SPM pollutants, and determine meteorological factors in the form of air humidity (RH), wind direction and speed on SPM concentrations. The results of the measurement of SPM concentration in Sorong are still in the very safe category because the concentration value is far from the quality standard value set by the government, with a value ranging from 16.04 – 30.44 ug/m3 per month. Judging from the source, the SPM particles in Sorong come from all directions. The results of the correlation of meteorological parameters with SPM concentration show that there is no significant relationship between humidity and SPM concentration, but there is a fairly strong relationship between wind speed and SPM concentration, with a correlation value of 0.766.